Mechanical properties and morphology of UV-cured glass fiber/epoxy acrylates composite / Mohamad Hafiz Mohd. Wahid - Mohd. Wahid, Mohamad Hafiz (2009)
The performance of the UV - cured glass fiber/epoxy acrylates composites has been investigated. Preliminary formulation of epoxy acrylates resin mixtures was done to select the most suitable formulation for this study. The woven glass fiber was used as the reinforcement in the composite and the layer used was varies. Coupling agent was incorporated to the other UV - cured samples to study the effects in strength. The thermal cured sample was fabricated to make comparisons between these two curing system. The testing conducted were tensile test, 3 - point bending test, FTTR and SEM. The strength increased with the increasing number of glass fiber layers and incorporation of coupling agent in the UV - cured samples. UV - cured samples having higher crosslink density that makes them having higher rigidity and stiffness compared to the thermal cured sample. Low crosslink density in thermal cured sample makes it exhibit more elastic property and give positive results in both tensile and flexural strain. However, the thermal cured sample easily fails under lower stress.